Limited role for extended maintenance temozolomide for newly diagnosed glioblastoma - Gramatzki, Dorothee; Vollmuth, Philipp; Hentschel, Bettina; Felsberg, Jörg; Herrlinger, Ulrich; Schmitz-Schackert, Gabriele; Tonn, Jörg-Christian; Westphal, Manfred; Sabel, Michael; Schlegel, Uwe; Wick, Wolfgang; Pietsch, Torsten; et al. (Neurology, 2017)
Objective: To explore an association with survival of modifying the current standard of care for patients with newly diagnosed glioblastoma of surgery followed by radiotherapy plus concurrent and 6 cycles of maintenance temozolomide chemotherapy (TMZ/RT → TMZ) by extending TMZ beyond 6 cycles. - Methods: The German Glioma Network cohort was screened for patients with newly diagnosed glioblastoma who received TMZ/RT → TMZ and completed ≥6 cycles of maintenance chemotherapy without progression. Associations of clinical patient characteristics, molecular markers, and residual tumor determined by magnetic resonance imaging after 6 cycles of TMZ with progression-free survival (PFS) and overall survival (OS) were analyzed with the log-rank test. Multivariate analyses using the Cox proportional hazards model were performed to assess associations of prolonged TMZ use with outcome. - Results: Sixty-one of 142 identified patients received at least 7 maintenance TMZ cycles (median 11, range 7-20). Patients with extended maintenance TMZ treatment had better PFS (20.5 months, 95% confidence interval [CI] 17.7-23.3, vs 17.2 months, 95% CI 10.2-24.2, p = 0.035) but not OS (32.6 months, 95% CI 28.9-36.4, vs 33.2 months, 95% CI 25.3-41.0, p = 0.126). However, there was no significant association of prolonged TMZ chemotherapy with PFS (hazard ratio [HR] = 0.8, 95% CI 0.4-1.6, p = 0.559) or OS (HR = 1.6, 95% CI 0.8-3.3, p = 0.218) adjusted for age, extent of resection, Karnofsky performance score, presence of residual tumor, O6-methylguanine DNA methyltransferase (MGMT) promoter methylation status, or isocitrate dehydrogenase (IDH) mutation status. - Conclusion: These data may not support the practice of prolonging maintenance TMZ chemotherapy beyond 6 cycles. - Classification of evidence: This study provides Class III evidence that in patients with newly diagnosed glioblastoma, prolonged TMZ chemotherapy does not significantly increase PFS or OS.